Pendampingan Mitigasi dan Adaptasi Perilaku Baru di Masa Pandemi Covid-19 Melalui Gerakan Masyarakat Menggunakan Masker (GEMAS), Penggunaan Antiseptik dan Desinfektan di Kabupaten Bombana, Sulawesi Tenggara - Nuralifah; Ruslin; Andi Nafisah Tendri Adjeng; Yuni Aryani Koedoes; Nur Fitriana Muhammad Ali (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
COVID-19 has become a global health problem and is declared a pandemic since December 2019. Indonesia is in the 4th highest population density in the world. The level of spread of COVID-19 in Indonesia may be more than in other countries with smaller populations. South East Sulawesi has confirmed 484 COVID-19 cases. One area with the highest number of patients is Bombana Regency. This community service was carried out by lecturers and students from Halu Oleo University which aimed to strengthen the role of the people of Bombana Regency in mitigating and adapting to the COVID-19 pandemic. The activities included education and socialization of GEMAS, antiseptics, and disinfectants which were carried out offline (door to door) and online, as well as the distribution of masks and spray hand sanitizer for free. This program is hoped to increase public knowledge and awareness in using masks, antiseptics, and disinfectants properly to face the COVID-19 pandemic.